2017
DOI: 10.1136/thoraxjnl-2017-210234
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of survivors, families and researchers on key outcomes for research in acute respiratory failure

Abstract: Patient, family and researcher groups supported inclusion of outcome domains that fit within the PICS framework. Patients and family members also supported many additional domains, emphasising the importance of including patients/family, along with researchers, in consensus processes to select core outcome domains for future research studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 45 publications
2
33
0
1
Order By: Relevance
“…44 This issue has been shown in previous studies, where patients and family members valued different outcomes when compared to researchers. 42 This study also gives new insights for future studies aiming to explore the differential response of patients with COPD to pulmonary rehabilitation. Although this qualitative study intended to inform the development of a core outcome set, future studies could focus on outcomes reported by these stakeholders that are seldom present in the literature, and yet highly meaningful not only to patients but also to their carers and health professionals.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…44 This issue has been shown in previous studies, where patients and family members valued different outcomes when compared to researchers. 42 This study also gives new insights for future studies aiming to explore the differential response of patients with COPD to pulmonary rehabilitation. Although this qualitative study intended to inform the development of a core outcome set, future studies could focus on outcomes reported by these stakeholders that are seldom present in the literature, and yet highly meaningful not only to patients but also to their carers and health professionals.…”
Section: Discussionmentioning
confidence: 88%
“…2 Similar results have been found for acute respiratory failure, where multiple life dimensions were considered essential to be measured by key stakeholders. 42 Thus, this study adds value to a future core outcome set that has the potential to improve the quality of care to patients with COPD, by being meaningful and useful for research and clinical practice in pulmonary rehabilitation. This study has some limitations that need to be acknowledged.…”
Section: Discussionmentioning
confidence: 95%
“…Understanding and information about critical illness within the family was important for the patient's recovery and for maintaining healthy family functioning. 22,23 Demonstrating the feelings that were exposed during the FamHC within the family improves the understanding of what each family member experiences during the ICU stay. The family members have concern for the critically ill and thoughts about how the roles and responsibilities within the family can change after returning home.…”
Section: Discussionmentioning
confidence: 99%
“…To address the issues of feasibility in ICU survivorship research, it is important to understand which minimum set of outcomes is most important for inclusion in all relevant research studies. Hence, we surveyed a national cohort of ARDS survivors ( n = 78) and family members ( n = 80), including 55 patient-family pairs, to empirically evaluate this issue [ 36 ▪▪ ].…”
Section: Patient and Family Perspectives On Patient Outcomes After Homentioning
confidence: 99%